Reframing public service radio: The case of BBC Sounds. (1st October 2021) - Charles-Hatt, Rachel-Ann; Sayers, Thomas
This study analyses the public service broadcast terrain within a changing sector that is driven by digital media convergence using the case of the BBC Sounds. From the findings, we demonstrate that the BBC Sounds promotes the idea of a visible media, an inter-medial platform providing agency to some of its listeners as they choose what content they want to listen to, while questioning whether this new streaming service offers more control than choice. In this study we identify issues surrounding accessibility for all when exploring on-demand content, and what impact this has on the public. Finally, we highlight the blurring of podcasts and radio and whether all live radio shows become, or risk becoming, podcasts.